2014
DOI: 10.4238/2014.june.9.11
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of serum high-sensitivity C-reactive protein and interleukin-6 in patients with acute coronary syndrome

Abstract: ABSTRACT. Serum high-sensitivity C-reactive protein (hs-CRP) is a sensitive indicator of inflammation, which is closely related with the progress of plaque formation. Interleukin-6 (IL-6) is one of the inflammatory markers of local coronary plaque and the peripheral blood cycle, promoting the occurrence of atherosclerosis development and plaque rupture. In this study, the correlation of hs-CRP and IL-6 was investigated in patients with acute coronary syndrome (ACS). Sixty cases of ACS, including 33 cases of ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
38
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(42 citation statements)
references
References 21 publications
0
38
0
2
Order By: Relevance
“…CRP and IL‐6 are plasma inflammatory markers that increase with aging heart (Franceschi & Campisi, ). Usually, their secretion could be predictive of subsequent cardiovascular events such as acute coronary syndrome (Wang, Liu, Wang, & Jin, ). It has been demonstrated that resveratrol suppresses the secretion of proinflammatory cytokines in murine macrophages by modulating NF‐κB signaling pathway (Ma, Wang, Dong, Li, & Cai, ).…”
Section: Discussionmentioning
confidence: 99%
“…CRP and IL‐6 are plasma inflammatory markers that increase with aging heart (Franceschi & Campisi, ). Usually, their secretion could be predictive of subsequent cardiovascular events such as acute coronary syndrome (Wang, Liu, Wang, & Jin, ). It has been demonstrated that resveratrol suppresses the secretion of proinflammatory cytokines in murine macrophages by modulating NF‐κB signaling pathway (Ma, Wang, Dong, Li, & Cai, ).…”
Section: Discussionmentioning
confidence: 99%
“…The former is involved in inflammatory cell activation and recruitment, and stimulates the liver to produce acute-phase proteins such as CRP while exerting a negative inotropic effect through myocardial nitric oxide synthase (NOS). Wang et al 55 found that IL-6 was related to the procession of ACS and had prognostic use. Serum IL-6 was shown to be useful for predicting mortality in patients with ACS51 and identifying individuals who could benefit from targeted interventional or intensive therapy 56.…”
Section: Summary Of Cardiac Biomarkersmentioning
confidence: 99%
“…In this study, the following results were assessed: correlation of high signal resolution along the vessel wall with hs-CRP and the frequent tendency of CAP and high CAM score in the high signal lesion positive group. The high value of hs-CRP in the positive group might reflect inflammatory change focused on the plaque lesions [7]. The high frequency of CAP and high CAM score were also evidence of an association of CAP and high signal resolution along the thoracic aorta on MRI.…”
mentioning
confidence: 87%